What defines 'enough' information? How policy workers make judgements and decisions during information seeking: preliminary results from an exploratory study - J.M. Berryman (Information Research: An International Electronic Journal)
Introduction. Reports findings from research in progress investigating judgment and decision making during information seeking in the workplace, in particular, the assessment of enough information. Characteristics of this judgment and the role of context in shaping it are framed against theories of human judgment and decision making. Method. Thirty-three semi-structured interviews were conducted with public sector policy workers in Australia. Two interviews were carried out, the first with individual participants and the second, a joint interview with two participants. Interviews were taped and transcribed and inductive data analysis carried out. Findings. Findings discussed in this paper focus on contextual factors that frame policy workers' judgment and decision making while information seeking, factors including ill-structured problems, shifting goals, time stress and action-feedback loops. Also revealed was the importance of developing a framework, against which the judgment of enough information can be made, and the fluid and iterative nature of these judgments. Conclusion. The contextual factors reported show similarities with those identified by naturalistic decision making researchers, suggesting this new field of decision theory has much to offer researchers into information seeking in context.